Baldwin I of Jerusalem, 1100-1118 - Edgington, Susan, author.
1 online resource.
Keywords: "Baldwin of Boulogne was born the youngest of three sons and marked out for a clerical career, yet in turn he became a First Crusader, first Latin count of Edessa and the founder of the Latin kingdom of Jerusalem. Nevertheless, remarkably, he has never been the subject of a full-length biography. This study examines in detail the stages of Baldwin's career, returning to the contemporary evidence to discover the qualities that enabled him not only to succeed his brother as ruler in 1100 but to maintain and expand the new kingdom of Jerusalem through the next eighteen years in the face of aggression from Muslim enemies and rivalry from fellow crusaders"--